Effect of two recombinant bovine somatotropin formulations on feeding behavior and metabolism of Holstein cows - Teixeira, Ritieli dos Santos; Araújo, Maria Carolina Narval de; Barbosa, Antônio Amaral; Almeida, Rodrigo de; Santos, Milene Lopes dos; Duarte, Letícia Alves Martins; Honorio, Vanessa Masson; Corrêa, Marcio Nunes; Pino, Francisco Augusto Burkert Del (Semina: Ciências Agrárias, 2024)
This study evaluated the effect of two commercial forms of recombinant bovine somatotropin (rbST; Later® and Fast®; 500 mg) on feed variability, feeding behavior, zootechnical parameters, and milk production of Holstein cows after peak production. Eighteen cows were randomly divided into two groups and treated with injectable of rbST every 14 days for 70 days. Blood samples were collected on day 1, 4, and 7 of each cycle, to assess circulating levels of non-esterified fatty acids (NEFA). Weight and body condition score (BCS) assessments were performed. Milk yields were measured daily using the DelPro™ software (DeLaval®). Feed consumption and feeding behavior was obtained daily using automatic individual feeders (Intergado®). No difference was observed in dry matter intake (DMI) between groups (P=0.07), and no impact was noted on dietary variability (P=0.64). In addition, animals treated with rbST-Fast exhibited more frequent visits to feeders, longer time in consumption, and higher relative DMI (per percentage of live weight) (P<0.01). Animals in the rbST-Fast group produced more milk than those in the rbST-Later group (P=0.03). Furthermore, the weight of the cows was significantly different (P=0.05) between groups. The weight of the rbST-Fast animals was smaller and varied more than thot of the rbST-Later animals (P <0.01). Nonetheless, no difference was noted in BCS (P=0.30) between the groups. The animals in the rbST-Fast group had higher concentrations of NEFA than those in the rbST-Later group (P<0.01). In conclusion, behavioral and metabolic shifts that sustained greater milk production in the cows receiving rbST-Fast. Nonetheless, these shifts are likely linked to lipomobilization and not dietary variability or consumption, as evidenced by the increase in NEFA and greater weight loss in that group.